Skin Penetration of Topical Epigallocatechin-3-Gallate (EGCG) as an Alternative Agent for Photoaging Prevention - Damayanti1,2, Cita Rosita Sigit Prakoeswa2 , Djoko Agus Purwanto3 , Anang Endaryanto4, Widjiati Widj (Institute of Medico-legal Publications Pvt Ltd, 2020)
Photoaging is skin aging, that especially caused by chronic exposure of ultraviolet radiation. Photoagingimpacts to patients’ quality of life. Many substances, such as green tea, had been tried to be alternativeagents for photoaging prevention. Epigallocatechin-3-gallate (EGCG) is the most abundant component ingreen tea. The requirement of topical substance to be able to work and give benefit to the skin is the skinpenetration. The aim of this study was to evaluate the skin penetration of EGCG. The back part of the maleWistar mouse was shaved carefully, then topical EGCG cream 5% and 10% were administered to mouseskin. After 1 week administration, the animal was terminated and the skin biopsy was done. The mouse skinwas extracted and high performance liquid chromatography (HPLC) examination was performed to evaluatethe skin penetration of topical EGCG. The result of HPLC examination of 2 ppm, 4 ppm, 6 ppm, and 8 ppmEGCG level, showed the curve peak at 3.295, 3.296, 3.295 and 3.293 second. The basic curve showed R2 ofpure EGCG powder used in this study was 0,9999. The result of HPLC examination in this study showed,the curve peak of extracted mouse skin after EGCG cream 5% and 10% administration were between 3.2-3.7second. The result of HPLC examination in this study showed that EGCG cream could penetrate into Wistarmouse skin after EGCG cream application for 1 week.